1997
DOI: 10.1016/s0896-6273(00)80956-3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel In Vitro Preparation: the Intact Hippocampal Formation

Abstract: The intact hippocampal formation (IHF) of neonatal or young rats can be kept alive for an extended period in a fully submerged chamber with excellent morphological preservation. Field or patch-clamp recordings, intracellular Ca2+ measurements, and 3-D reconstruction of biocytin-filled neurons can be performed routinely. The generation and propagation of network-driven activities can be studied within the IHF or between connected intact structures such as the septum and the hippocampus or two hippocampi, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
145
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 30 publications
3
145
0
Order By: Relevance
“…Hippocampal transverse slices (thickness of 0.6 -0.7 mm) were cut with a VT 1000S vibroslicer (Leica, Nussloch, Germany) and kept in oxygenated (95% O 2 -5% CO 2 ) aCSF at room temperature (20 -22°C) at least 1 hr before use. Unusually thick hippocampal slices were used to preserve the advantages of the intact hippocampal preparation in vitro (Khalilov et al, 1997). There was no correlation between extracellularly recorded action potential frequency and electrode depth, indicating that, if the oxygen tension was lower in the center of our 700-m-thick slices, it did not affect neuronal or network excitability.…”
Section: Methodsmentioning
confidence: 99%
“…Hippocampal transverse slices (thickness of 0.6 -0.7 mm) were cut with a VT 1000S vibroslicer (Leica, Nussloch, Germany) and kept in oxygenated (95% O 2 -5% CO 2 ) aCSF at room temperature (20 -22°C) at least 1 hr before use. Unusually thick hippocampal slices were used to preserve the advantages of the intact hippocampal preparation in vitro (Khalilov et al, 1997). There was no correlation between extracellularly recorded action potential frequency and electrode depth, indicating that, if the oxygen tension was lower in the center of our 700-m-thick slices, it did not affect neuronal or network excitability.…”
Section: Methodsmentioning
confidence: 99%
“…In a chilled and perfused bath, the brain was cut into the left and right hemisphere, and the complete hippocampus, including the septum, was extracted from each hemisphere. This preparation maintains the whole 3D hippocampal architecture, preserving cellular and axonal integrity (32,33). Freshly extracted preparations were placed in a chamber and perfused with oxygenated (95% O 2 /5% CO 2 ) ACSF (126 mM NaCl, 3.5 mM KCl, 2 mM CaCl 2 , 1.3 mM MgCl 2 , 1.2 mM NaH 2 PO 4 , 26.2 mM NaHCO 3 , and 10 mM glucose).…”
mentioning
confidence: 99%
“…In this study, long-lasting ictal discharges (30-250 s) could be induced by applying solutions containing the GABA A receptor antagonist bicuculline, the glutamate receptor agonist kainate, or high K + while only brief interictal activities were recorded in age-matched slices under similar conditions. In addition to allow measurement of intracellular changes in [Ca 2+ ] using confocal microscopy from groups of neurons loaded extracellularly with Fluo 3-AM, Khalilov et al (1997) demonstrated that electrical stimulation of the septum inhibited the firing of hippocampal CA3 stratum oriens interneurons; this finding thus confirmed the existence of GABAergic projections from the septum to hippocampal interneurons (Freund and Antal, 1988).…”
Section: Isolated Hippocampimentioning
confidence: 80%
“…This preparation has also allowed the demonstration that ictal discharges induced by bath application of kainic acid originate from the hippocampus and propagate to the septum, since they disappear in the septum following its surgical separation from the hippocampus (Khalilov et al, 1997). Finally, by employing field potential or dual whole-cell recordings from the two interconnected hippocampi it was shown that unilateral application of medium containing high Mg 2+ or tetrodotoxin blocked the propagation of the ictal discharge generated in the contralateral hippocampus by high extracellular [K + ].…”
Section: Isolated Hippocampimentioning
confidence: 99%